THE USE OF ACCOUNTING INFORMATION: WHAT ARE THINGS THAT INFLUENCE IT? - Permatasari, Ditya; Nawirah, Nawirah; Aprilianti, Adinda Putri (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
The widespread growth of online shops, which are sales conducted through the internet, can contribute to the emergence of a digital economy, providing evidence of the advancement of information technology. In Indonesia, online shop businesses have witnessed remarkable growth in the digital service sector, surpassing the convenience offered by traditional stores. This research aims to examine the impact of Business Owner's Perception, Accounting Knowledge, and Business Scale on the utilization of Accounting Information among students from the Faculty of Economics at Maulana Malik Ibrahim State Islamic University, Malang, who operate online shop businesses. The research methodology employed in this study is quantitative in nature, employing a descriptive approach. Data collection is carried out through the distribution of questionnaires. The population of this study consists of all students from the Faculty of Economics at Maulana Malik Ibrahim State Islamic University, Malang. The sample size of 48 respondents is selected using non-probability sampling, specifically the purposive sampling method. The collected data will be analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression tests. The findings of this study indicate that owner's perception and business scale significantly influence the utilization of accounting information in online shop businesses. However, the variable of accounting knowledge does not have a significant effect on the utilization of accounting information in online shop businesses. In conclusion, higher owner perception and business scale positively impact the utilization of accounting information among online shop business owners.